Revealed Preference Analysis for Mode Choice in Graduate Level Engineering Students of Kathmandu Valley - Chataut, Piyush; Shrestha, Pradeep Kumar (Journal of Advanced College of Engineering and Management, 2021)
Proper planning which is the key element in ensuring infrastructure efficiency, relies on demand analysis. Among the various trips under the domain of demand analysis educational trips occupy a significant part and hence the knowledge about patterns and attitudes of these trips is important to policymakers and infrastructure planners. The current study analyzes the mode choice of graduate-level engineering students in Kathmandu valley where the current transportation system is facing multiple problems thus requiring a proper planning intervention. This study reveals the educational mode preference among the students of engineering colleges. The reveal preference survey was conducted at the various engineering colleges in Kathmandu valley. The study concludes that the travel distance, number of siblings, and vehicle ownership effects the selection of personal modes of transport and distance effects the selection of public transportation, walking option being base criteria for both the cases. It is recommended that existing walking conditions should be improved within the educational zones while public transport which are preferred options for long journeys be designed considering movement between zones.